If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(m + 2) = 30 Reorder the terms: 3(2 + m) = 30 (2 * 3 + m * 3) = 30 (6 + 3m) = 30 Solving 6 + 3m = 30 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 3m = 30 + -6 Combine like terms: 6 + -6 = 0 0 + 3m = 30 + -6 3m = 30 + -6 Combine like terms: 30 + -6 = 24 3m = 24 Divide each side by '3'. m = 8 Simplifying m = 8
| 5-6x=-13 | | 51=3x+15 | | 3x^2-2=0 | | 4x-3=2x+17 | | p+3=2p+1 | | (2b+3)+b=15 | | .5w-1.32+1.2w=.4w+8.04 | | 2(n+2)=16 | | 3n-7=-19 | | -15=-3(4t-3) | | 3r+7=-8 | | -12=-3x | | 2(3g+2)=4(g+4) | | 2x+3=x+12 | | 3-12-3=-12 | | .20x+.05(18-x)=.10(-18) | | 0.78=1.2p-2.52 | | 3(x+7)=7x-15 | | 3(x-2)(x-5)=0 | | -1-4k=-37 | | 2=5b+12 | | 15-3x=27-7x | | 3-5x=23 | | 3n+5=2n+10 | | x-3x+24+(-12)=24 | | 2x+1=6m+1 | | 13+2c=1+4c | | 14x^2=29 | | 6(3)-4+9=7 | | C^2-x=6 | | 35=5+c+2c | | 4+m+3m=24 |